Methodological Rigor in Health Research: Ensuring the Best Approach to Address Clinical and Public Health Objectives - Heru Santoso Wahito Nugroho (Humanistic Network for Science and Technology (HNST), 2026)
In health research, the credibility and clinical relevance of scientific evidence are fundamentally determined by how well research methods are designed, justified, and reported. The methods section serves as the critical link between research objectives and the evidence generated to address them. However, misalignment between objectives and methodological approaches remains a common concern, often resulting in biased findings, limited applicability, and compromised decision-making in clinical and public health contexts. This editorial emphasizes that methodological rigor must be understood primarily as the alignment between research objectives and the chosen methods. The “best” method is not necessarily the most advanced, but the one most appropriate for answering a clearly defined clinical or public health question. Through conceptual discussion and illustrative examples across qualitative, experimental, and observational research, this paper highlights how inappropriate methodological choices can undermine validity, distort interpretations, and weaken the applicability of findings. The editorial further outlines a systematic approach to achieving alignment, beginning with the precise formulation of research objectives and followed by the careful selection and justification of study design, population, data collection procedures, and analytical strategies. Transparency in reporting and adherence to ethical standards are emphasized as essential components in demonstrating this alignment and ensuring reproducibility. As a key message to authors, this paper underscores that methodological decisions must not be driven by convention or convenience, but by their capacity to directly and reliably answer the research question. Failure to ensure such alignment risks producing evidence that is not fit for purpose, with potential implications for patient care and health policy. Conversely, a well-aligned and transparently reported methodological framework strengthens the validity, credibility, and impact of research, thereby supporting evidence-based healthcare and improved health outcomes.Keywords: health research; methodological rigor; research objectives; study design; clinical validity; transparency; reproducibility